O50 Variation in postendoscopy upper gastrointestinal cancer across endoscopy providers in England: a population-based study. (19th June 2022) - Kamran, Umair; Evison, Felicity; Rutter, Matt; Adderley, Nicola; Brookes, Matthew; Morris, Eva; Burr, Nick; Valori, Roland; McCord, Mimi; Trudgill, Nigel
Abstract : Introduction: Post endoscopy upper gastrointestinal cancer (PEUGIC) is proposed as a key performance indicator by the British Society of Gastroenterology. We have examined the incidence of PEUGIC within 3 years of endoscopy (PEUGIC-3yr) in England. Methods: Using linked National Cancer Registration and Analysis Service and Hospital Episode Statistics databases, all patients diagnosed with upper gastrointestinal cancer (UGIC) between 2009 and 2018 who underwent endoscopy in the three years prior to UGIC diagnosis were identified. Endoscopies without a cancer diagnosis 6 to 36 months prior to UGIC diagnosis were defined as false negative endoscopies (FN). Endoscopies within 6 months of UGIC diagnosis were true positive endoscopies (TP). The PEUGIC-3yr rate was calculated as the proportion of FN out of the sum of TP and FN endoscopies. PEUGIC-3yr rates were calculated in relation to patients' demographics and UGIC characteristics. Funnel plots with superimposed control limits representing two and three standard deviations from the mean were produced to assess variations in PEUGIC endoscopies rates between trusts. Results: 106, 728 endoscopies in 98, 801 patients were included. The overall unadjusted PEUGIC-3yr rate was 8.5 (95% CI 8.34–8.70)% and remained unchanged over the study period. Rates were higher in younger patients (9.2% in patients aged ≤60 vs 7.2% in patients aged ≥80, p<0.001), females (9.3% vs 8.2%, p<0.001) and patients with increasing comorbidity score ≥5 (27.7% vs 5.6%, p<0.001). PEUGIC-3yr rate in patients with Barrett's oesophagus was 21%. PEUGIC-3yr rates were higher in upper third compared to lower third of oesophagus cancers (10.6% vs 7.4%, p<0.001) and distal compared to proximal stomach cancers (7.6% vs 6.9%, p 0.04). The PEUGIC-3yr rate was higher for UGIC diagnosed at earlier clinical stage I compared to stage IV (18.1% vs 5.5%, p<0.001). The PEUGIC rate varied from 7.6% to 39.3% among NHS trusts ( Figure 1 ). Private providers had higher PEUGIC-3yr rate than NHS providers, 10.1% vs 8.5%, p 0.014. Conclusion: The substantial variation in PEUGIC rates among endoscopy providers in England highlights large potential variation in endoscopy quality and decision making during and after endoscopy.